2020
DOI: 10.18326/muqtasid.v11i2.104-116
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Determinant Analysis in Islamic Bank in Indonesia

Abstract: This study is aimed to discover efficiency determinant factors of Islamic banks in Indonesia to maintain financial system stability. Financial data of 11 Islamic Banks in Indonesia was obtained from 2010-2019. Purposive sampling method is employed to determine the obtained-sample with the availability of financial statements as criteria. There are two analysis data methods, firstly, Data Envelopment Analysis (DEA) is employed to calculate the efficiency score and analyze the efficiency condition of Islamic banks, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
3
7
1
Order By: Relevance
“…The most efficient bank was the full-fledged Islamic Bank with the most significant asset ownership, BSM. This finding is consistent with previous studies, such as those by Devi & Firmansyah (2020), Darlis & Utary (2022), Jiménez-Hernández et al (2019, Kamarudin et al (2019), andLotto (2019), which suggest that larger banks have more resources and capabilities that can positively impact efficiency. This condition is due to several factors, such as larger companies having more resources like capital, labor, and technology to enhance their operational performance, better risk management capabilities, and more significant opportunities to improve efficiency through broader market access and economies of scale (Darlis & Utary, 2022;Devi & Firmansyah, 2020;Miftahurrohman, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The most efficient bank was the full-fledged Islamic Bank with the most significant asset ownership, BSM. This finding is consistent with previous studies, such as those by Devi & Firmansyah (2020), Darlis & Utary (2022), Jiménez-Hernández et al (2019, Kamarudin et al (2019), andLotto (2019), which suggest that larger banks have more resources and capabilities that can positively impact efficiency. This condition is due to several factors, such as larger companies having more resources like capital, labor, and technology to enhance their operational performance, better risk management capabilities, and more significant opportunities to improve efficiency through broader market access and economies of scale (Darlis & Utary, 2022;Devi & Firmansyah, 2020;Miftahurrohman, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…This result means that profitability significantly impacts the efficiency of the Islamic banks (Sari & Saraswati, 2017;Bayuny & Haron, 2017). However, the findings of this research are in contrast with those of Miftahurrohman (2019), Devi & Firmansyah (2020), and Koiri & Erdkhadifa (2022), who found that profitability does not have a significant impact on efficiency. Meanwhile, research conducted by Darlis & Utary (2022) found that profitability has a negative impact on efficiency.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Efficiency is becoming a key indication for the banking sector's contribution to a country's financial system stability (Devi & Firmansyah, 2020). According to Mirzaei and Moore (2014), industries that rely significantly on bank financing will grow quicker and be boosted by the emergence of new busineses in nations with effective banking systems.…”
Section: Literature Reviewmentioning
confidence: 99%